Potential of Purple Sweet Potato Ethanol Extract (Ipomea Batata L.) to Prevent Skin Aging in Menopausal Wistar Rats - Wiryanthini, Ida Ayu Dewi; Sutadarma, I Wayan Gede; Dewi, Ni Putu Ratih Cahaya; Aryaweda, Made Dhiyo Wiweka (Faculty of Medicine, Public Health, and Nursing, 2025)
Background: Menopause is a hypo-estrogenic condition due to decreased ovarian function, a natural thing experienced by women between the ages of 45 and 55, causing health problems on the skin, in the form of decreased collagen production so that skin elasticity decreases, and is prone to dry conditions, sagging to fine lines and wrinkles as a sign of skin aging also called Estrogen Deficient Skin (EDS). This study aims to determine the role of anthocyanin activity in purple sweet potatoes as phytoestrogens to overcome skin symptoms caused by EDS in the form of proliferation of collagen-forming cells, namely fibroblast cells in Wistar rats with a menopause model. Method: This research is purely experimental with the method Post Test Only Control Group Design which aims to determine the effect of administering purple sweet potato ethanol extract on the number of fibroblast cells in the skin tissue of Wistar rats with a menopause model. A total of 16 female Wistar rats aged 12 weeks that were bilaterally ovariectomized were divided into 2 groups, namely group P0 given 1 ml/day of distilled water, group P1 given ethanol extract of purple sweet potato at a dose of 400 mg/kg BW/day for 3 months. On the last day of treatment, the experimental animals were terminated and then skin tissue was taken to make histological preparations of Masson's Trichrome and to examine the number of fibroblast cells. Results: Data analysis using the Independent T test obtained significant results p=0.00 and Post Hoc LSD obtained significant results p<0.05 for all comparisons across groups. Conclusion: Based on these results, it can be concluded that Anthocyanin in ethanol extract of purple sweet potato can increase fibroblast cell proliferation in skin tissue of Wistar rats with a menopause model. Further research is still needed on other parameters to prove the role of Anthocyanin as a phytoestrogen to overcome EDS.